Pengaruh Motivasi dan Kompensasi Terhadap Kinerja Petani Bawang Merah (The Influence of Motivation and Compensation on the Performance of Shallot Farmers) - Oktaviani, Dewi Anggun; Sulistyowati, Retno; Lidyana, Novita (Study Program of Agribusiness, Faculty of Agriculture, University of Wijaya Kusuma Surabay, 2025)
This study analyzes the influence of motivation and compensation on the performance of shallot farmers in Randuputih Village, Probolinggo. Quantitative methods were used with a sample of 40 farmers who are members of the local Shallot Farmers Group Association. Data were collected through questionnaires and interviews, then analyzed using multiple linear regression. The results showed: Motivation (X1) and compensation (X2) have a significant effect simultaneously on performance (Y) (sig. <0.05; R²=0.459) Partially, both variabels have a positive effect with compensation as the dominant factor (coefficient 0.452). This finding indicates that increasing compensation has a greater impact on farmer performance than motivation. This study recommends the need for policies that focus on improving the compensation system to encourage the productivity of shallot farmers.Keywords: Motivation, Compensation and Farmer Performance.